Species Variety of the Calf and Human-Attracted Mosquitoes in Southwest Iran - Parvaneh Faraji-Fard; Kambiz Ahmadi-Angali; Abdolamir Behbahani (Tehran University of Medical Sciences, 2022)
Background: Any mosquito control methods requires precise information about population dynamics, variety, biology and mosquito habitat. This research assessed Culicid mosquitoes' attraction to a human host and a calf to better understand their behavior. Methods: Adult mosquitoes were sampled in 22 weeks in southwestern Iran's Nur Ali Village from May to October 2015. The mosquitoes were drawn to the person and calf as bait, while the unbaited trap was also used. A substantial statistical difference between attracted mosquitoes to the hosts was determined in the T-test. Results: Within 22 weeks, 29821 mosquitoes were captured. Only 9% were collected from the human baited net trap, 89.1% from the calf baited net trap, and 1.9% from the unbaited net trap. The number of collected female mosquitoes was statistically significantly higher using the calf baited net trap of the total mosquitoes, 916 were randomly identified at the species level by local identification keys. Of these, 63 were Anopheles stephensi (human: 16%, calf: 75% and unbaited: 9%), 83 An. pulcherrimus (human: 27%, calf: 60% and unbaited: 13%), 118 Aedes caspius (human: 24%, calf: 69% and unbaited: 7%), 493 Culex tritaeniorhynchus (human: 52%, calf: 37% and unbaited: 11%), 153 Cx. quinquefasciatus (human: 44%, calf: 47% and unbaited: 9%), and 6 Cx. theileri (human: 33%, calf: 50% and unbaited: 17%). Conclusion: The obtained results here provide useful insights into the mosquito population and the possibility of using this information as an essential part of integrated vector management regarding the reemergence of malaria or other mosquito-borne.